2019
DOI: 10.4103/uros.uros_152_18
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dutasteride and Tomato Extract Combination on Reducing Blood Loss after Transurethral Resection of the Prostate

Abstract: Context: Lycopene, a carotenoid found in tomatoes, possesses antiangiogenic activities that might be useful in the management of prostate enlargement. However, the current evidence is still inconclusive in regard to this matter. Aims: The aim of the study was to investigate the effect of combined oral dutasteride and lycopene consumption in reducing posttransurethral resection of the prostate (TURP) bleeding. Settings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Vol. 21 No. 4 October -December 2023 0.02; ΔHct 5.68 % ± 2.56% vs. 6.52 % ± 2.39 %, respectively, p = 0.04) (Table 4)…”
Section: Jaimcmentioning
confidence: 99%
“…Vol. 21 No. 4 October -December 2023 0.02; ΔHct 5.68 % ± 2.56% vs. 6.52 % ± 2.39 %, respectively, p = 0.04) (Table 4)…”
Section: Jaimcmentioning
confidence: 99%
“…Finally, the anti-inflammatory and healing properties of oral lycopene along with dutasteride treatment on reducing transurethral resection of the prostate (TURP) bleeding were examined by Nugroho et al in 2019 [ 168 ]. Twenty-two patients diagnosed with BPH were randomly assigned to two groups ( n = 11 each).…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%
“…The mean MVD in the control group was significantly higher versus the intervention group (28.2 ± 12.3 vs. 18.3 ± 7.6 vessel/mm 2 ) and reduction of post-TURP plasma erythrocytes was significantly higher in the control group compared to the intervention group (−0.34 ± 0.18 vs. −0.17 ± 0.12). The results suggested that daily consumption of dutasteride and lycopene for at least 30 days reduced the formation of blood vessels in the prostate and reduced blood loss in post-TURP examinations [ 168 ].…”
Section: Nutraceutical Therapies For Bphmentioning
confidence: 99%